Measuring the maturity of carbon market in China: An entropy-based TOPSIS approach. (20th August 2019) - Liu, Xianfeng; Zhou, Xinxing; Zhu, Bangzhu; He, Kaijian; Wang, Ping
Abstract: In this study, we construct an evaluation index system in terms of three dimensions including internal, external and interface factors. We propose an entropy-based TOPSIS model to measure the maturity of carbon market. The proposed model uses the entropy method to objectively weight the indicators, and the TOPSIS method to measure the maturity of carbon market. Taking China's seven pilot carbon markets from 2013 to 2017 as an example, the empirical results are that the overall maturity of China's pilot carbon markets is relatively low, for the sake of small market size, low market effectiveness, low market activeness and high price volatility. Moreover, due to the difference in the quotas transaction volume, market liquidity and market supporting facilities, there are obvious differences in maturities among China's seven pilot carbon markets. In 2017, the maturity of Hubei market is the highest, reaching 0.6146. The maturity of Guangdong, Shenzhen, Beijing, Shanghai and Tianjin reaches 0.6108、0.5022、0.4351、0.4267 and 0.3888 respectively. The maturity of Chongqing market is the only 0.3633, at the lowest level. What's more, from the perspective of maturity evolution trend, Hubei, Guangdong and Shenzhen fluctuate upward from the market opening to 2017 and steadily rank in the top three. Shanghai and Tianjin show a U-shaped growth trend, declining from 2013 to 2015 and continuing to rise from 2015 to 2017. Beijing shows a fluctuating downward trend from 2013 to 2017, while ranking fourth. Chongqing ranks relatively low, but it shows an escalating trend. Finally, several targeted policy implications are put forward to enhance the maturities of carbon markets. Highlights: An evaluation index system of internal, external and interface factors is proposed to examine the maturity of carbon market. An entropy-based TOPSIS model is proposed to measure the maturity of carbon market. The empirical results show that the overall maturity of China's pilot carbon markets is relatively low. There are obvious differences in maturities among China's seven pilot carbon markets.